Cone Penetration Testing 2022 : Proceedings of the 5th International Symposium on Cone Penetration Testing (CPT'22), 8-10 June 2022, Bologna, Italy. - Gottardi, Guido. (Taylor & Francis Group, 2022)
This book provides a full picture of the current knowledge and major trends in CPT research and development, with respect to innovations in instrumentation, latest advances in data interpretation, and emerging fields of CPT applications.